Conducting an Industry and competitive analysis of the gypsum industry in Russia by the example of JSC Khabez Gypsum Plant - A. G. Chekalov (Вестник Северо-Кавказского федерального университета)
Introduction. In order to reduce risks and improve the efficiency of their operations, industrial companies should conduct their own research aimed at studying key competitors and the industry as a whole. This stage is one of the most important on which the future development strategy of the organization is based. As an example, the article discusses the methods of competitive analysis produced for the analysis of JSC Khabez Gypsum Plant. Goal. To conduct a comparative analysis of the competitiveness of the enterprise under study with other companies in the gypsum industry. Materials and methods. The study provides a competitive analysis of the largest companies. The methodological basis of the work consists of classical methods of industry analysis (SWOT analysis) and competitive analysis methodology based on comparative analysis tools. As a result of the research, the author proposed additional industry indicators specific to gypsum production and influencing the competitive environment of this market.Results and discussion. In the course of the work, it was found that the organization under study has a high level of competitiveness, allowing it to maintain successful economic activity in the market, competing in the market with such large manufacturers as Knauf Gypsum LLC.Conclusion. Based on the conducted research, it can be said that the Russian gypsum production market is still far from its maximum, which follows from the growth rates of the companies shown in the tables. The task of large organizations seems to be to strengthen the current position of a monopolist or maintain the largest market share through innovative products, equipment modernization and maintaining low prices. Small firms will have to improve their marketing strategies, establish a sales market, implement a good personnel policy, etc. to ensure the growth of the organization.